Development of low cost data acquisition system for mobile satellite signal performance measurement - Ibrahim, Abba (Universiti Malaysia Sarawak (UNIMAS), 2012)
The satellite radio wave passes through the open space environment experiences a fading effect as a result of ionospheric effect, rain attenuation, multi path effect, radio noise and design ofthe antenna. Another loss mechanism is the absorption of atmospheric gases for earth tenninal with extremely low elevation angles to the satellite at frequencies 1-2 GHz. The elevation angle is relativel y large for most of the handheld GPS recei ver' s use, There is need for experimental data in the less developed and developing countries such as Africa, Asia and Latin America for the study and analysis of mobile satellite (MS) signal performance for communication purposes. The experiment is carried out in open area with no obstruction of the direct wave. In addition, National Marine Electronics Association (NMEA) sentences are used to obtain the required signal propagation parameters. Comparison is made between the previous methods conducted in Fukuoka, Japan of using Handheld GPS receiver to acquire propagation data with the current method developed in Kota Samarahan in tenn of the operational compatibility when used on other operating system software. Data acquisition system developments were designed to manage the open space environment satellite propagation data. The systems were integrated with adaptive graphical user interface (AGUI), to evaluate the signal perfonnance in tenn of Signal to Noise Ratio (SNR), azimuth angles and satellite elevation angles. The analysis produced fonns an important part in the studies of the signal performance. From this research work, MS received signals for Kota Samarahan was characterized in order to provide quality services to the users in the environment. The hyper-tenninal intercepts and adaptive graphic user interface were used to evaluate the previous data acquisition system conducted in Fukuoka and Stuttgart. The analysis for ionospheric effect on MS was conducted by comparing data obtained in Kota Samarahan with the data obtained in Fukuoka. The experimental work was conducted with reduced cost and simple equipments so as to encourage more experimental studies on MS signal perfonnance. Future research studies can be done by designing a program that will link and monitor the pilot data acquisition system placed in remote areas. Rain sensor and satellite display view can be added to the AGUI.